Moonlighting Proteins: Unveiling Their Multifunctionality in Metabolic Regulation and Drug Discovery - Prajapati, Shatrudhan; Singh, Ajay Pal; Bhadouria, Namrata (Current Drug Metabolism, 2025)
Moonlighting proteins, defined by their ability to perform distinct, independent functions beyond their primary roles, have garnered attention in metabolic regulation and drug discovery. This review highlights the emerging significance of these proteins in diverse physiological and pathological processes. With examples like glycolytic enzymes and Krebs cycle components, we explore their involvement in transcriptional regulation, immune responses, and stress modulation. Their unique ability to mediate host-pathogen interactions and disease progression underscores their potential as therapeutic targets. Advanced technologies, such as proteomics and bioinformatics, have revolutionized the identification and characterization of these proteins, unraveling their structural and functional complexities. This synthesis aims to bridge gaps in understanding protein multifunctionality and advocates its implications in drug development. By targeting specific functions of moonlighting proteins while preserving their essential roles, new strategies in pharmacology and personalized medicine are envisioned. The review also proposes a roadmap for leveraging these proteins' multifunctionality to address current challenges in therapeutic interventions.
Keywords: protein multifunctionality